A super-elderly case of abdominal aortic aneurysm associated with chronic disseminated intravascular coagulation. Issue 2 (February 2015) - Otsui, Kazunori; Yamamoto, Mai; Aoki, Humiaki; Ozawa, Toru; Domoto, Koji; Suzuki, Atsushi; Iwata, Sachiyo; Takei, Asumi; Inamoto, Shinya; Inoue, Nobutaka
Abstract Chronic disseminated intravascular coagulation (DIC) is a well-known complication of aortic aneurysm. A 91-year-old Japanese woman was admitted to our hospital because of massive purpura of the lower limbs. The presence of abdominal aortic aneurysm (AAA) had been pointed out from the age of 80 years, and its diameter had gradually increased. The AAA was composed of two portions, that is, a large upper and a small lower portion, and a large mural thrombosis was observed in the lower portion. The laboratory data led to the diagnosis of DIC, and AAA was the only identifiable cause of coagulopathy. The time course of exacerbation of AAA was consistent with the progression of thrombocytopenia and purpura. Therefore, we concluded that AAA was the underlying cause of DIC. Since DIC in aortic aneurysms is associated with excessive fibrinolysis, tranexamic acid was administered as anti-fibrinolytic therapy. After that, coagulopathy was drastically improved. Our patient responded successfully to anti-fibrinolytic therapy for coagulopathy. The present case illustrates the importance of evaluation of the diameter of an aneurysm as well as intraluminal thrombosis, which may play an important role in coagulopathy including DIC. It is necessary to monitor coagulation and fibrinolysis for the follow-up of patients with AAA. <Learning objective: We present a case report of an aged Japanese woman with abdominal aortic aneurysm associated with disseminated intravascular coagulation, and anti-fibrinolytic therapy drastically ameliorated her condition. Our case illustrates the importance of evaluation of the diameter of an aneurysm as well as conducting follow-up monitoring of coagulation and fibrinolysis.>